Lead intoxication in two canines. Biochemical confirmation, specific treatment and review of most reported organic alterations in Veterinary Medicine (Veterinary Science, 2024)
Pet poisoning in veterinary medicine occurs relatively often, although it represents a small percentage of the wide variety of pathological entities the generalpractitioner faces in daily practice (bacterial, parasitic, metabolic, traumatic, surgical). In turn, within toxic etiologies, those produced by heavy metals are rarelyreported today (in order of importance, poisonings produced by warfarinrodenticides, pesticides, human use medications, toxins, garbage, veterinary usemedications, toxic plants and foods are described). This report describes two cases of patients that suffered lead poisoning, presenting practically all the clinical signs historically reported by available literature. Despite being a scarcely frequent entity due to the heavy metal’s low availability, we consider that having knowledge aboutthe systems that are affected by such exposure, both chronically and acutely, is very important, irrespective of whether they are chronic or acute, since there arealterations that are lethal, and which when recognized in time, enable making a definite biochemistry diagnosis and establishing a specific healing treatment. But the potential sequels that such poisoning can leave, as well as its specific treatment must not be overlooked. To such end, the need to have veterinarian toxicological laboratories and suitable advising lines in place is emphasized.
Keywords: Lead intoxication; toxicologic urgencies; Calcium disodium edetate; Heavy metals